2013
DOI: 10.1002/jso.23414
|View full text |Cite
|
Sign up to set email alerts
|

Survival of current production tumor endoprostheses: Complications, functional results, and a comparative statistical analysis

Abstract: Therapeutic study, level IV-1 (case series).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
82
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 41 publications
7
82
1
4
Order By: Relevance
“…Alternative treatments have been associated with dislocation, infection, nonunion, and disease progression, often requiring reoperation. Intraoperative complications such as hypotension, oxygen desaturation, embolization, and cardiac arrest have also been reported [2,9,12,22,24,[26][27][28]. Of note, Barwood et al [4] reported acute oxygen desaturation and hypertension in 11 of 45 patients treated with intramedullary nail fixation for metastatic tumors of the femur with actual or impending fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative treatments have been associated with dislocation, infection, nonunion, and disease progression, often requiring reoperation. Intraoperative complications such as hypotension, oxygen desaturation, embolization, and cardiac arrest have also been reported [2,9,12,22,24,[26][27][28]. Of note, Barwood et al [4] reported acute oxygen desaturation and hypertension in 11 of 45 patients treated with intramedullary nail fixation for metastatic tumors of the femur with actual or impending fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperatively, the median total MSTS score (measured at most recent followup) for the entire group of patients was 21 (range, , the median ECOG score was 2 (range, 0-3, 68% B 2), and the median KPS score was 60 (range, 40-100). For the 11 patients with at least 1 year of followup, the median total MSTS score (measured at most recent followup) was 27 (range, [21][22][23][24][25][26][27][28][29][30], the median ECOG score was 1 (range, 0-2, 100% B 2), and the median KPS score was 80 (range, 60-100). For the remaining 11 patients with less than 1 year of followup, the median total MSTS score (measured at most recent followup) was 11 (range, 5-25), the median ECOG score was 3 (range, 1-3, 36% B 2), and the median KPS score was 40 (range, 40-80).…”
mentioning
confidence: 99%
“…Prosthetic replacement with modular implants has become the most common reconstructive technique of bone loss of the lower limb after tumor resection [1,16,17,25,26,31,33,34]. The same modular systems may be used to restore osteoarticular defects of the hip and knee in prosthetic revision surgery and posttraumatic situations [6,14,32].…”
Section: Introductionmentioning
confidence: 99%
“…Severe femoral bone deficiency after fracture or loosening of a prior stem traditionally results in revision to a cemented or largediameter press-fit stemmed implant, an allograft-prosthetic composite (APC) reconstruction, or a total femur replacement [7,23,26,33]. Unfortunately, short residual proximal femur segments cannot be addressed by these options and these constructs have high failure rates, often exceeding 30% at 5 years [20,22,23,26,29,33]. We need to improve our current strategies to preserve or reconstitute the remaining femoral bone stock while creating a more durable revision construct.…”
Section: Introductionmentioning
confidence: 99%